2023
DOI: 10.1021/acs.nanolett.3c02231
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Doped Plasmonic Nanocrystal Metamaterials

Kihoon Kim,
Zachary M. Sherman,
Angela Cleri
et al.

Abstract: Assembling plasmonic nanocrystals in regular superlattices can produce effective optical properties not found in homogeneous materials. However, the range of these metamaterial properties is limited when a single nanocrystal composition is selected for the constituent meta-atoms. Here, we show how continuously varying doping at two length scales, the atomic and nanocrystal scales, enables tuning of both the frequency and bandwidth of the collective plasmon resonance in nanocrystal-based metasurfaces, while the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 62 publications
6
34
0
Order By: Relevance
“…To integrate the NCs with the photonic cavity, we placed a water droplet on top of the Ge spacer, then dispensed a droplet containing oleate-capped ITO NCs (dispersed in 2:1 hexane:toluene) on top. As we previously reported, , slow evaporation of the solvent produces a compact monolayer of ITO NCs (Figure a). Although Akselrod et al showed that isolated NCs on the top of a spacer-PEC geometry can exhibit perfect absorption behavior, close-packed layers of NCs increase their extinction , (and thus, the imaginary part of permittivity) due to the collective plasmon coupling behavior.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…To integrate the NCs with the photonic cavity, we placed a water droplet on top of the Ge spacer, then dispensed a droplet containing oleate-capped ITO NCs (dispersed in 2:1 hexane:toluene) on top. As we previously reported, , slow evaporation of the solvent produces a compact monolayer of ITO NCs (Figure a). Although Akselrod et al showed that isolated NCs on the top of a spacer-PEC geometry can exhibit perfect absorption behavior, close-packed layers of NCs increase their extinction , (and thus, the imaginary part of permittivity) due to the collective plasmon coupling behavior.…”
Section: Resultssupporting
confidence: 75%
“…Close-packed monolayer films of ITO NCs exhibit a resonant peak in their optical extinction spectra and associated effective complex permittivity similar to other resonantly absorbing materials, as shown schematically in Figure a. As shown previously, ITO NC monolayer films have a distinct extinction peak [Figure a (ii)], which is associated with the CPR of the NC array (at λ CPR ). Due to the dense packing and uniformity of the monolayer film, its optical properties are well represented by an effective complex permittivity with a finite width, resonant absorption feature, centered at the peak wavelength of the CPR of the NC array, as shown in Figure a (iii).…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations